Vision for Teaching Communication Skills through Literary Texts in BBS Second Year (Journal of Management, 2023)
The article discusses the rationale and process of teaching Vision: A thematic anthology of literary and cultural texts in BBS second year in Tribhuvan University, Nepal. This book is a collection of multicultural literary readings that consist of poetry, fiction, prose and play. Based on the ideas that literary readings and their creative discussions in a classroom helps the learners to develop their creative, critical and language skills to be used in their professional life, the article has discussed how the texts incorporated in this textbook are appropriate to achieve these objectives of the course. The readings on the logics of using literature in the university classes form the theoretical background of this study. The study has concluded that the use of literary texts in management classes in the university helps the learners develop the basic communicative skills keeping the humanitarian aspect at focus. The article also incorporates a practical process of teaching a poem from this textbook in the real classroom and discusses how it could help students develop the expected skills.